ANALISIS ASUHAN KEPERAWATAN INTERVENSI INOVASI TERAPI KOMBINASI ALOE VERA GEL DAN OLIVE OIL UNTUK MENCEGAH TERJADINYA PRESSURE ULCER PADA PASIEN KRITIS DI RUANG INTENSIVE CARE UNIT (ICU) - Annisa Kirana Putri (2023)
Pressure Ulcer (PU) is a local injury to the skin or underlying tissue that occurs in bony prominences and is caused by pressure or friction. This scientific work aims to analyze the needs of the community with innovative interventions in providing combination therapy of Aloe vera gel and olive oil to prevent the occurrence of Pressure Ulcers in critical patients in the Intensive Care Unit (ICU) room. After 7 days of intervention, the results showed that the Braden scale scores tended to be stable and the patient did not experience pressure ulcers. This success cannot be separated from other intervention standards. Based on the results of the analysis of the innovative combination therapy intervention of Aloe Vera Gel and Olive Oil, it can be concluded that this intervention provides an effective prevention effort to prevent the occurrence of pressure ulcers in critical patients in the Intensive Care Unit (ICU).